Inclusive Manufacturing: The Impact of Disability Diversity on Productivity in a Work Integration Social Enterprise - Narayanan, Sriram; Terris, Ed (Manufacturing and Service Operations Management, 2020)
Problem definition: This study examines the impact of disability diversity on the productivity of apparel manufacturing teams in the context of a work integration social enterprise. Two measures of disability diversity are examined: the number of disability categories employed in a production line and the evenness of disability category dispersion among workers employed in an apparel production line. Academic/practical relevance: The problem has both academic and practical relevance. From an academic standpoint, the current literature does not study the implications of employing individuals with disabilities and their impact on productivity with microdata. The issue also has practical relevance because it ties into recent managerial interest to employ individuals with disabilities in organizations. According to statistics, only 35% of workers with disabilities have some form of significant full-time employment. Methodology: The study uses panel regression analyses to test the impact of disability diversity (number of disability categories and evenness of disability category dispersion) of workers in a production line using detailed multiyear data on the productivity of apparel manufacturing cells. Results: Two key insights emerged from the analyses. First, productivity can be enhanced by increasing the diversity of workers with disabilities in the workforce within a garment-manufacturing cell. Specifically, productivity is best at moderate levels of disability categories in a team. Second, team productivity is higher at greater levels of evenness of disability category dispersion. Managerial implications: The analysis in this paper sheds light on the potential benefits of integrating individuals with disabilities into organizations and its implications on productivity. Specifically, the study finds evidence that having moderate levels of disability categories on a team with higher levels of evenness in disability category dispersion is associated with better productivity rather than having a concentrated team focused on a specific disability. The implications of the results and limitations for the study as well as its potential insights into the context of social enterprises that employ individuals with disabilities are discussed.